2017
DOI: 10.1111/jfpp.13389
|View full text |Cite
|
Sign up to set email alerts
|

Quality changes and microbiological spoilage analysis of air-packed and vacuum-packed silver carp (Hypophthalmichthys molitrix ) fillets during chilled storage

Abstract: The effects of air‐packed (AP) and vacuum‐packed (VP) on quality and microbial characteristics of silver carp (Hypophthalmichthys molitrix) fillets during chilled storage (4 ± 1 °C) were investigated. The fillets were analyzed for sensory scores, total volatile basic nitrogen (TVB‐N), ATP‐related compounds (ATP, IMP, HxR, and Hx), K value, and biogenic amines (BAs). The results proved that VP inhibited the increase of microorganisms, TVB‐N, Hx, and putrescine in silver carp, and slowed the reduction in sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The APC, TVB-N, psychrophilic bacteria, and K value indicators compiled, indicated that there was a close relationship between them. It is known that the growth of bacteria is responsible for the high increase in the TVB-N and K value (Li et al, 2017a). It is hypothesized that the loss of trapped water contributes to a decrease in muscle tenderness and an increase in free water.…”
Section: Pca Of the Bigeye Tunamentioning
confidence: 99%
“…The APC, TVB-N, psychrophilic bacteria, and K value indicators compiled, indicated that there was a close relationship between them. It is known that the growth of bacteria is responsible for the high increase in the TVB-N and K value (Li et al, 2017a). It is hypothesized that the loss of trapped water contributes to a decrease in muscle tenderness and an increase in free water.…”
Section: Pca Of the Bigeye Tunamentioning
confidence: 99%
“…TBA values can be used to characterize the degree of aquatic product fat oxidation . Moreover, TVB‐N value is one of the most important attributes in evaluating fish quality, and the accepted TVB‐N value of aquatic product is less than 30 mg 100 g −1 . Importantly, the degradation of adenosine triphosphate (ATP) of the fish is related positively to the loss of fish freshness during the storage .…”
Section: Resultsmentioning
confidence: 99%
“…To assess the microbial load, samples with nine-fold dilutions were inoculated in agar plates. [4,29] Ten-gram sample was grounded and homogenized; the homogenates were then diluted to the level of 10 2−8 . Inoculums (1 mL) were transferred on a sterile agar plate.…”
Section: Total Bacterial Countmentioning
confidence: 99%
“…Another potential reason for the color change might be the chemical reactions induced by increasing activity of acidic proteases. [29] Coordinate a/b is related to substance decomposition, mainly from the oxygen-lysis states of protein and fat. There were similar trends in b values of fresh samples and 0.2% CGA-treated samples during storage; while there were similar trends in 0.5% and 0.7% CGA-treated samples in storage.…”
Section: Color Changes During Storagementioning
confidence: 99%